Reverie - La Sala, Ryan (Sourcebooks Fire, 2022)
Kane Montgomery is found half-dead in a river, with no memory of how he got there and why his life seems so incredibly different now. Reality itself seems different. Three strangers arrive to help Kane find out what is going on, claiming to be his friends from before. Worlds begin to materialize out of nowhere--the gym becomes a subterranean temple, an historic house becomes a Victorian mansion--and a sinister evil arises, threatening to alter reality forever.